2019
DOI: 10.3390/app9020232
|View full text |Cite
|
Sign up to set email alerts
|

Quadratic Electro-Optic Effect in Metal Nanoparticles in a Transparent Dielectric Medium

Abstract: The quadratic electro-optic effect/Kerr coefficients were measured for the first time for metal nanoparticles. In particular, gold nanoparticles in glass were studied. Measurements were made using the field-induced birefringence method at a wavelength near the onset of the surface plasmon resonance. The magnitudes of the Kerr coefficients for different sizes of gold nanoparticles in glass were measured and compared with that of subnanometer size metallic particles in non-conjugated conductive polymers. The mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
3
7
0
Order By: Relevance
“…Comparing with doped nonconjugated conductive polymer, the increase roughly goes as d −3 , where d is the nanoparticle-diameter. This is identical to the dependence of the real part of Kerr coefficient (K) on d as reported earlier [6]. For quadratic electro-optic measurements, the magnitudes of modulations were large enough to measure for all three sizes of gold nanoparticles in glass [6].…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…Comparing with doped nonconjugated conductive polymer, the increase roughly goes as d −3 , where d is the nanoparticle-diameter. This is identical to the dependence of the real part of Kerr coefficient (K) on d as reported earlier [6]. For quadratic electro-optic measurements, the magnitudes of modulations were large enough to measure for all three sizes of gold nanoparticles in glass [6].…”
Section: Resultssupporting
confidence: 84%
“…Saturation of absorption and two-photon absorption in specific nanometallic systems have also been studied [1][2][3][4][5][6][7][8][9][10][11][12]. Very recently, we have reported quadratic electro-optic effect in metallic nanoparticles within dielectric media [6]. As our literature review has revealed no measurement of electroabsorption in metal nanoparticles has been published or known in the prior art.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations